AXIOLOGICAL APPROACH AS A TOOL FOR SHAPING PROFESSIONAL IDENTITY OF FUTURE MUSIC TEACHERS - Nabijonov Ravshanbek Obidjon o‘g‘li (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article examines the role of the axiological approach in shaping the professional identity of future music teachers. It explores how integrating values, ethical principles, and cultural awareness into music education fosters the development of professional competencies, creativity, and pedagogical responsibility. The study highlights interactive and innovative methods that support reflective practice, ethical reasoning, and holistic professional growth. By applying an axiological perspective, music teacher training programs can prepare educators who are both technically competent and culturally and ethically grounded.